Optical Detection of Distal Lung Enzyme Activity in Human Inflammatory Lung Disease - Alicia Megia-Fernandez; Adam Marshall; Ahsan R. Akram; Bethany Mills; Sunay V. Chankeshwara; Emma Scholefield; Amy Miele; Bruce C. McGorum; Chesney Michaels; Nathan Knighton; Tom Vercauteren; Francois Lacombe; et al. (BME Frontiers, 2021)
Objective and Impact Statement. There is a need to develop platforms delineating inflammatory biology of the distal human lung. We describe a platform technology approach to detect in situ enzyme activity and observe drug inhibition in the distal human lung using a combination of matrix metalloproteinase (MMP) optical reporters, fibered confocal fluorescence microscopy (FCFM), and a bespoke delivery device. Introduction. The development of new therapeutic agents is hindered by the lack of in vivo in situ experimental methodologies that can rapidly evaluate the biological activity or drug-target engagement in patients. Methods. We optimised a novel highly quenched optical molecular reporter of enzyme activity (FIB One) and developed a translational pathway for in-human assessment. Results. We demonstrate the specificity for matrix metalloproteases (MMPs) 2, 9, and 13 and probe dequenching within physiological levels of MMPs and feasibility of imaging within whole lung models in preclinical settings. Subsequently, in a first-in-human exploratory experimental medicine study of patients with fibroproliferative lung disease, we demonstrate, through FCFM, the MMP activity in the alveolar space measured through FIB One fluorescence increase (with pharmacological inhibition). Conclusion. This translational in situ approach enables a new methodology to demonstrate active drug target effects of the distal lung and consequently may inform therapeutic drug development pathways.